Forced harmonic vibrations of multi‐span Euler‐Bernoulli beams carrying spring‐damper‐mass systems. Issue 1 (25th January 2021) - Klanner, Michael; Ellermann, Katrin
Abstract: A spring‐damper‐mass system can be used as a passive vibration absorber, which can reduce the vibration amplitudes of a system at certain frequencies or in a broad band. In this paper, a highly efficient computational method called Numerical Assembly Technique (NAT) is extended to vibration problems of beams under arbitrarily distributed loads carrying spring‐damper‐mass systems, to identify the optimal set of parameters of the passive vibration absorbers. The method is quasi‐analytical in the sense that the governing equations are fulfilled exactly and only minor numerical errors due to double‐precision arithmetic are introduced in the boundary and interface conditions.